Metal doped mesoporous FeOOH nanorods for high performance supercapacitors. Issue 77 (20th October 2017) - Barik, Rasmita; Jena, Bikash Kumar; Mohapatra, Mamata
Abstract : In the present study, the effect of doping of foreign atoms on the parent atoms and the application of the resultant material for energy storage are successfully investigated. Abstract : In the present study, the effect of doping of foreign atoms on the parent atoms and the application of the resultant material for energy storage are successfully investigated. A facile method is reported for successful incorporation of cobalt into the regular crystal lattice of iron oxide in ethylene glycol media. As iron oxides are reasonable, the Co doped nano-goethite is expected to be of potential use for supercapacitor application with a high specific capacitance value of 463.18 F g −1 at 0.1 A g −1 current density. It shows a cycling stability of 1000 at 1 A g −1 with 96.36% of initial capacitance. The doped goethite nanorod with a band gap of 2.82 eV and high surface area (159.74 m 2 g −1 ) was found to be a superior electrode material for supercapacitors in terms of specific capacitance and cycling capability at a particular percentage of doping. The high discharge capacitance and its retention are attributed to high surface area and porosity of the doped iron oxide.